The usage of humor as a coping mechanism towards the academic performance of undergraduate students - Nugroho, Raden Arif Adi; Pritasari, Adita (Journal of Business and Management, 2020)
Abstract. Coping mechanisms can be defined as efforts to master, reduce, or tolerate demand or strain. Coping mechanisms aim to provide the user with a state of well-being. Humor is one of the available coping mechanisms. Humor, when being used as a coping mechanism, may help undergraduate students to perform better in their academic performance during times of crisis. In this case, undergraduate students have to endure a crisis-based online learning environment which proves to be more difficult than the usual with the presence of a strain (pandemic crisis). The research aims to determine the relationship between humor in general and the different types of humor as a coping mechanism and the academic performance of undergraduate students in a crisis-based online learning environment. The research uses primary data generated from a simple random sampling technique using an online questionnaire that was distributed to respondents and secondary data from journals and literature. The respondents of this research are 389 undergraduate students from the Bandung Institute of Technology (ITB). The data is analyzed using a Multiple Linear Regression and Pearson Correlation Method. The result shows that humor correlates positively with the academic performance of undergraduate students in a crisis-based online learning environment, albeit very weak or very small. The benign types of humor correlate positively with the academic performance of undergraduate students in a crisis-based online learning environment with a very low to a strong degree of strength. This research is unable to conclude the relationship between the injurious types of humor and the academic performance of undergraduate students in a crisis-based online learning environment due to statistically insignificant data. The findings of the research recommend practitioners such as undergraduate students and universities not to overuse humor as a coping mechanism to increase academic performance in a crisis-based online learning environment. The research also recommends using self-enhancing humor to build a crisis-based online learning environment with a sense of humor to make it easier to respond to crisis conditions. Future research may add moderating variables and greater sample size to approve or disprove the findings of this research.Keywords: Coping Mechanism, Humor, Academic Performance, Undergraduate Students